(untitled) (Mongolian Journal of Agricultural Sciences, 2014)
In this article we analyze the effect of sowing date on yield of Sudan grass green mass. The study was conducted over 2 years on the basis of working farms in the dry steppe zone of Kazakhstan. The yield of Sudan grass green mass is depending on the most favorable sowing dates. DOI: http://dx.doi.org/10.5564/mjas.v11i2.219 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.63-67